EVALUATING AND COMPARING SEARCH FEATURES OF ACADEMIC LIBRARIES; USER PERCEPTIONS OF LIBRARIES WEB METASEARCH ENGINES: A CHECKLIST-BASED APPROACH - Moghaddam, Alireza Isfandyari; Movaffagh, Zohreh Bahari (Malaysian Journal of Library and Information Science, 2010)
This paper aims at evaluating and comparing search features of Web metasearch engines (MSEs). To do this, a total of 64 MSEs were identified and examined on the basis of first observations. However after examining them, about 70% of these MSEs were discarded and 19 cases, which were free of charge, accessible and compatible with the research objectives were kept for further analysis. A researcher-made checklist, composed of 50 items under five search engines’ general criteria (search operators, restrictors, result presentation, search help options and others) was used for data collection. It was found that AND, Phrase, Number of results per page, Keeping query searched, and Help were features that have been fully included in all 19 MSEs, while the features Anchor search and Size have been neglected by the MSEs examined. It should be also added that featuresm Truncation, Keywords in title, URL, and Brief text have been highly supported by 18 cases (94.7%). The features Date, Cached, and Also try were observed only in one case (5.3%). It is suggested that the checklist used in this study be restructured for studying search features of Web search engines, digital libraries and other Internet search tools.